2014
DOI: 10.1098/rspb.2014.0830
|View full text |Cite
|
Sign up to set email alerts
|

Senescence or selective disappearance? Age trajectories of body mass in wild and captive populations of a small-bodied primate

Abstract: Classic theories of ageing consider extrinsic mortality (EM) a major factor in shaping longevity and ageing, yet most studies of functional ageing focus on species with low EM. This bias may cause overestimation of the influence of senescent declines in performance over condition-dependent mortality on demographic processes across taxa. To simultaneously investigate the roles of functional senescence (FS) and intrinsic, extrinsic and condition-dependent mortality in a species with a high predation risk in natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
125
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(137 citation statements)
references
References 78 publications
(147 reference statements)
12
125
0
Order By: Relevance
“…In spring, a decrease in body mass of old females was exhibited at lower elevation (down‐valley). The age‐dependent decrease is in line with predictions from classical senescence theories (Medawar, 1952; Williams, 1957) and concurs with other studies that found body mass senescence in mammals (Beirne et al., 2015; Hämäläinen et al., 2014; Nussey et al., 2011; Tafani et al., 2013; Weladji et al., 2010). Indeed, age‐dependent body mass senescence has previously been found in a closely related species, the Alpine marmot (Tafani et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In spring, a decrease in body mass of old females was exhibited at lower elevation (down‐valley). The age‐dependent decrease is in line with predictions from classical senescence theories (Medawar, 1952; Williams, 1957) and concurs with other studies that found body mass senescence in mammals (Beirne et al., 2015; Hämäläinen et al., 2014; Nussey et al., 2011; Tafani et al., 2013; Weladji et al., 2010). Indeed, age‐dependent body mass senescence has previously been found in a closely related species, the Alpine marmot (Tafani et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, in late summer, state‐dependent effects were expressed as a terminal decrease in mass over the last year of life, again only in females living at lower elevation. This result is consistent with most other recent studies on body mass senescence, which also reported terminal effects (Beirne et al., 2015; Douhard et al., 2017; Hämäläinen et al., 2014; Hammers et al., 2012; Nussey et al., 2011; Tafani et al., 2013). While a variety of factors could potentially lead to terminal decreases, it is commonly suggested that they indicate terminal illness, causing a sudden collapse in condition prior to death (Coulson & Fairweather, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…are the smallest extant primates. Their average life span in the wild is 2-3 years, although some gray mouse lemurs (M. murinus) may live for 10 years or more (Hämäläinen et al, 2014). Mouse lemurs usually produce one litter per year (Eberle and Kappeler, 2006).…”
Section: Introductionmentioning
confidence: 99%